Blue Water Trade‐Offs With Vegetation in a CO2‐Enriched Climate. Issue 7 (6th April 2018) - Mankin, Justin S.; Seager, Richard; Smerdon, Jason E.; Cook, Benjamin I.; Williams, A. Park; Horton, Radley M.
Abstract: Present and future freshwater availability and drought risks are physically tied to the responses of surface vegetation to increasing CO2 . A single‐model large ensemble identifies the occurrence of colocated warming‐ and CO2 ‐induced leaf area index increases with summer soil moisture declines. This pattern of "greening" and "drying, " which occurs over 42% of global vegetated land area, is largely attributable to changes in the partitioning of precipitation at the land surface away from runoff and toward terrestrial vegetation ecosystems. Changes in runoff and ecosystem partitioning are inversely related, with changes in runoff partitioning being governed by changes in precipitation (mean and extremes) and ecosystem partitioning being governed by ecosystem water use and surface resistance to evapotranspiration (ET). Projections show that warming‐influenced and CO2 ‐enriched terrestrial vegetation ecosystems use water that historically would have been partitioned to runoff over 48% of global vegetated land areas, largely in Western North America, the Amazon, and Europe, many of the same regions with colocated greening and drying. These results have implications for how water available for people will change in response to anthropogenic warming and raise important questions about model representations of vegetation water responses to high CO2 . Plain Language Summary: Using a large ensemble of simulations from a state‐of‐the‐art Earth System Model, we show that 42% of global vegetated land areas are projected to have "greening" in the form of additional vegetation growth at the same time as "drying" in the form of reduced soil moisture in a business‐as‐usual world. Simultaneous greening and drying is curious and suggests that future ecosystems—which could demand more water due to warmer and longer growing seasons and CO2 fertilization—siphon water that historically would have become the runoff that fills rivers and streams, termed "blue water." We show that warming and changes in plant growth from CO2 creates an explicit water trade‐off in which future vegetation directly diminishes runoff relatively or absolutely for nearly half of global land areas. Our results have important implications for future water availability, but also point to the crucial importance of resolving model uncertainties associated with terrestrial vegetation and its response to increasing CO2 . Key Points: Vegetation "greening" and soil "drying" cooccurs over 42% of global vegetated land in a large GCM ensemble The greening and drying pattern is driven by changes in precipitation partitioning at the land surface These results highlight an intrinsic future trade‐off between terrestrial vegetation (green water) versus total runoff (blue water)